Stress & Symbiosis: Heads or Tails? - Bénard, Alexis; Vavre, Fabrice; Kremer, Natacha (Frontiers in Ecology and Evolution, 2020)
An increasing number of organisms are subjected to abiotic (e.g., air, water and soil quality, temperature), but also biotic (e.g., new pathogens) stressors. These stressors may disturb the chemical and physiological homeostasis of living systems, and thus impact their ecology and evolution. Because eukaryotes are often associated with symbionts, these changes do not only impact the host but rather the holobiont, an assemblage of interacting species. Indeed, stressors can modify the symbiotic community composition and functions directly, but also indirectly through their impact on host physiology. Any disruption of the symbiotic homeostasis can then impact the host fitness. On the other side, several symbionts protect their host against various threats, and they may facilitate the adaptation of the holobiont to the new environment by limiting the negative impact of stress on the host. It now remains to clarify if their presence constitutes a driver of adaptation of the host or an obstacle limiting the selection of adaptive traits in the host, and to discuss if symbiosis is always the optimal strategy to cope with stressors. The reciprocal impact between stress and symbiosis can become more complex when stressors are considered in combination, as it occurs in nature. Indeed, synergistic or antagonistic effects may impact the holobiont response, and studies characterizing individual disturbances may not be sufficient. In the current context of climate change and globalized pollution, it is thus crucial to develop integrative approaches to predict how organisms, communities and ecosystems will face combinations of stressors.